Pengaruh Locus of Control terhadap Career Maturity pada Fresh Graduate di Kota Bandung - Fathiya Jasmine Noor Indira; Sartika, Dewi; Saefudin, Muhamad Arif (UNISBA Press, 2024)
Abstract. Locus of Control pertains to individuals' beliefs about the factors that shape their lives, whether these are internal, such as personal confidence, or external, like the influence of others or luck. Career Maturity, in contrast, evaluates how prepared someone is to make sound career decisions, considering elements like career planning, exploration, understanding of the working world, and decision-making skills. The issue of insufficient Career Maturity among college graduates in Bandung underscores the need to explore whether Locus of Control plays a role in this area. This study targeted fresh graduates in Bandung, using convenience sampling to collect data from 315 respondents through questionnaires. The study utilized Career Maturity measures from Super, refined by Sartika (2003) and re-evaluated by Hakim (2022), alongside the IPC Locus of Control Scale by Levenson, adapted by Faizah, Nasehudin, & Nurizzati (2023). Employing multiple linear regression analysis within a quantitative framework, the research found that Locus of Control has a 67% positive effect on Career Maturity, with the internal dimension having the strongest influence (β = 0.371). Abstrak. Locus of Control merujuk pada keyakinan individu tentang faktor-faktor yang memengaruhi kehidupan mereka, baik itu faktor internal seperti kepercayaan diri pribadi, maupun faktor eksternal seperti pengaruh orang lain atau keberuntungan. Di sisi lain, Kematangan Karir mengevaluasi seberapa siap seseorang untuk membuat keputusan karir yang tepat, dengan mempertimbangkan elemen-elemen seperti perencanaan karir, eksplorasi, pemahaman tentang dunia kerja, dan keterampilan pengambilan keputusan. Masalah kurangnya Kematangan Karir di kalangan lulusan perguruan tinggi di Bandung menekankan pentingnya mengeksplorasi apakah Locus of Control berperan dalam hal ini. Penelitian ini menargetkan fresh graduate di Bandung, dengan menggunakan convenience sampling untuk mengumpulkan data dari 315 responden melalui kuesioner. Studi ini menggunakan ukuran Kematangan Karir dari Super, yang disempurnakan oleh Sartika (2003) dan dievaluasi ulang oleh Hakim (2022), bersama dengan IPC Locus of Control Scale oleh Levenson yang diadaptasi oleh Faizah, Nasehudin, & Nurizzati (2023). Dengan menggunakan teknik analisis regresi linier berganda dalam kerangka kerja kuantitatif, penelitian ini menemukan bahwa Locus of Control memiliki pengaruh positif sebesar 67% terhadap Kematangan Karir, dengan dimensi internal memiliki pengaruh paling kuat (β = 0.371).